Manajemen Pengelolaan Dana SBSN di Kementerian Agama Tahun 2016-2019 - Medina, Desmi Avicena (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
The construction of facilities originating from State Sharia Securities (SBSN) funds has made an important contribution to increasing access to services of public interest. Using a qualitative approach , this study shows that the SBSN Fund Management System at the Ministry of Religion has supported the implementation of infrastructure development programs for the provision of religious education services, hajj services, socio-religious services and other religious services. Although it has generally been declared successful in the construction of facilities originating from SBSN funds, the constraints faced remain so that continuous innovation is needed in the construction of SBSN facilities within the Ministry of Religion